THE EFFECT OF GREEN MARKETING AND PRODUCT QUALITY ON PURCHASING DECISIONS FOR COCONUT SHELL CRAFTS AT YANDE BATOK UMKM IN KLUNGKUNG REGENCY - Anggreni, I Dewa Ayu Wulan (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Ngurah Rai, 2025)
In the modern business world, environmentally conscious marketing is becoming increasingly popular. There are various ways to implement environmentally focused marketing strategies, such as using recycled materials as raw materials for production and using eco-friendly packaging. Additionally, companies can engage in social activities or donations that aim to preserve the environment. This study aims to determine the partial and simultaneous effects of green marketing and product quality on the purchasing decisions of coconut shell craft products in the Yande Batok MSMEs (Micro, Small, and Medium Enterprises) in Klungkung Regency. Data were collected through the distribution of questionnaires to respondents aged 17 years and above who have purchased Yande Batok products, totaling 160 respondents. The data were processed and analyzed using multiple linear regression. The results of the study indicate that both Green Marketing and Product Quality, simultaneously, have a significant positive influence on the Purchasing Decisions of Yande Batok MSMEs in Klungkung Regency. Green Marketing, partially, has a positive and significant impact on the Purchasing Decisions of Yande Batok MSMEs in Klungkung Regency. Product Quality, partially, also has a positive and significant impact on the Purchasing Decisions of Yande Batok MSMEs in Klungkung Regency